THE TRANSFORMATION OF ISLAMIC IDENTITY BEHIND THE SCREEN: Indonesian Horror Films, 1980-2020 (JOURNAL OF INDONESIAN ISLAM, 2025)
This study examines the representation of Islamic identity in Indonesian horror films from the 1980s to the 2020s. Employing an interpretive qualitative method, this study analyzes selected horror films from each decade to uncover patterns of change in the portrayal of Islamic identity through narrative, symbolism, and character depiction. The findings reveal three key trends: first, during the 1980s and 1990s, Islamic identity was prominently depicted through characters such as Kiai or Ustaz, who served as exorcists. Second, in the 2000s, representations of Islamic identity diminished, replaced by themes of secularism and eroticism. Third, in the 2020s, Islamic identity re-emerged more explicitly, with stronger Islamic themes present in both storylines and visual symbols. These findings suggest that the portrayal of Islam in Indonesian horror films reflects not only the socio-cultural dynamics of society but also market strategies aimed at appealing to a predominantly Muslim audience. This research contributes to interdisciplinary studies on Islam, popular culture, and Indonesian film while paving the way for further inquiries into the relationship between religion and mass media.